CCNP Security Firewall 642-617 quick reference - Mason, Andrew (Cisco Press, 2011)
As a final exam preparation tool, the CCNP Security Firewall 642-617 Quick Reference provides a concise review of all objectives on the new CCNP Security Firewall exam (642-617). This eBook provides you with detailed, graphical-based information, highlighting only the key topics in cram-style format. With this document as your guide, you will review topics on firewall basics, the ASA product family, ASA configuration with both the CLI and ASDM, ASA access control, ASA network integration, AAA configuration, and ASA HA. This fact-filled Quick Reference allows you to get all-important information at a glance, helping you to focus your study on areas of weakness and to enhance memory retention of essential exam concepts. TOC Cisco Firewall and ASA Technology Basic Connectivity and Device Management ASA Access Control ASA Network Integration AAA Configuration on the Cisco ASA ASA High Availability About the author: Andrew G. Mason, CCIE No. 7144, CISSP, is a security consultant and co-founder of the UK based RandomStorm Limited. Andrew has 17 years experience in the IT industry, working in Internet security for the past several years. He is involved in the design and implementation of security deployments for numerous clients based upon Cisco technology. He is also a CHECK Team Leader and leads penetration tests for many UK and international clients. About the Technical Editor: Max Leitch, CCIE No. 20178, is a network and security architect/engineer and an independent consultant. He holds CCNP, CCDP, CCSP, and CCIE Security certifications.
Resource description page (viewed Apr. 7, 2011)
Keywords: Computer networks -- Security measures; Firewalls (Computer security); Réseaux d'ordinateurs; Sécurité; Mesures; Coupe-feu (Sécurité informatique); Computer networks; Security measures; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications; Electronic resource